(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Pandemic threat made the social body sick, even before the COVID-19 virus attacked the individual’s health. When Romania started the lockdown in March 2020, interpersonal relationships began to strain, and extreme behaviours appeared, never seen before. It could see the gradual escalation of social tensions due to the limitation of a large part of fundamental rights. The State’s decisions to prevent Pandemic is seen as an abusive interference on the Churches’ internal activity. The rites and rituals of the Orthodox Church, the religious denomination with the most significant number of believers in Romania, were either forbidden or distorted by the uninspired intervention of public authorities. Gradually, tensions between the State and the Church intensified to the point where public accusations against the State began to appear, in the public speech of the bishops and especially of Patriarch Daniel, the Romanian’s spiritual leader Orthodox Church. Do the State and its intervention in the activity of the Church affect the dignity of the human being? Does Religion’s resistance to the social tension caused by the Pandemic express a high degree of resilience? Are the pressures between State and Church profound, or did the Pandemic superficially generate them? How will religious life in Romania be affected after the Pandemic? What will be the post-pandemic challenges that spiritual life has to face? We will study official institutional documents, press comments, and specialists’ opinions expressed in the literature to answer these complicated questions. We will also try to assess, based on statistical information, whether the phenomenon of secularisation has been accelerated or diminished during the Pandemic restrictions. Our approach’s limitations are that the Pandemic is an evolving process, and the conclusions still cannot be clear and convincing. However, we will try to predict the evolution of religious life in the post- pandemic period. Our analysis will fall within the interdisciplinary field of sociology of religion, social sciences, legal sciences and contemporary history.